A CAD tool for an array of differential oscillators coupled through a broadband network. Issue 2 (22nd August 2012) - Ionita, M.; Cordeau, D.; Paillot, J. M.; Bachir, S.; Iordache, M.
Abstract A new expression of the equations describing the locked states of two oscillators coupled through a resistor is presented in this article. This theory has led to the elaboration of a CAD tool which provides, in a short simulation time, the frequency locking region of two coupled differential oscillators. © 2012 Wiley Periodicals, Inc. Int J RF and Microwave CAE, 2012.